AB1123 Poor assessment of risk of osteoporosis after a forearm fracture in women: a health insurance database study in the loire valley region (france). (15th June 2017) - Cattelain-Lopez, E; Lin, D Chu Miow; Goupille, P; Happe, A; Lespessailles, E; Jacquot, F; Tauveron, P; Rusch, E; Oger, E; Mulleman, D
Abstract : Background: Bone Mineral density (BMD) assessment is a useful tool to evaluate bone fragility and is largely recommended in patients at risk of osteoporosis. We have previously reported in 250 women aged 50 year-old or more that only ≈ 10% of them had a BMD after a forearm fracture (1). Objectives: Herein, we evaluated BMD assessment and prescription of anti-osteoporotic drugs after a forearm fracture in women after 50 year-old in a large population database. Methods: We identified all forearm fractures in women aged 50 years old or more in the "Centre-Val de Loire, France" area between 01/01/2011 and 31/12/2012, using the National Health Insurance database which cover both private and public sectors of the whole population. We analyzed the reimbursement and determinants of BMD assessment such as age, consumption of drugs inducing osteoporosis, anti-osteoporotics drugs and long term illnesses. Results: We identified 4120 women with a forearm fracture during the study period. Among them, 546 (13.25%) had a BMD assessment performed at a median time of 4 months after the fracture. Women who had had a BMD were significantly yonger than those who had not (67.44 years versus 74.63 years: OR=0.941 CI95% (0.932–0.949)). Anti-aromatase treatment was positively associated with BMD assessment (OR=3.233 (CI95%: 1.976–5.290)) while corticosteroid were not (OR=0.866 (CI95%: 0.601–1.247)). Among the women who had a BMD assessment, 168/546 (30.77%) had an anti-osteoporotic drug initiated after the forearm fracture, versus 231/3574 (6.46%) in those who had no BMD performed (p<0.05). Conclusions: In this large population, less than 15 percent of women over 50 year-old have a BMD assessment after a forearm fracture. BMD assessment was associated with anti-osteoporotic drugs initiation. References: Erny F, Auvinet A, Chu Miow Lin D, et al (2015) Management of osteoporosis in women after forearm fracture: data from a French health insurance database. Joint Bone Spine: 82:52–55. Acknowledgements: We thank Caroline Rault, department of Pharmaco-epidemiology, Rennes and Florence Erny, department of Rheumatology, Tours for their support and contribution in this project. This work would not have been possible without the help of Mehdi Gabbas "Caisse National d'assurance Maladie" (CNAM-TS), Valérie Edel, "Institut des données de Santé" (IDS), and the "Institut National de la Santé de de la Recherche Médicale" (Inserm). This study has been funded by the "groupe de recherche et d'investigation sur l'ostéoporose" (GRIO) and by the "Association Français de lutte anti-Rhumatismale" (AFLAR). This work is the result of the "Prevention of osteoporosis after distal forearm fracture – Prévention de l'Ostéoporose après fracture du Poignet (POP)" study group. Disclosure of Interest: None declared